PENGARUH MOTIVASI KERJA DAN GAYA KEPEMIMPINAN SERTA KONTRIBUSINYA TERHADAP KINERJA PEGAWAI REKAM MEDIS DI RSUD KABUPATEN KARAWANG (PENELITIAN PADA PEGAWAI INSTALASI REKAM MEDIS RSUD KAB.KARAWANG) - Ridwan .; Yuyus Suryana (Magister Manajemen Pascasarjana Universitas Langlangbuana, 2021)
The Effect of Work Motivation and Leadership Style and Their Contribution to the Performance of Medical Record Employees at the Karawang Regency Hospital. (Research on Medical Record Installation Staff at RSUD Kab. Karawang). This study aims to examine and analyze the relationship between work motivation and leadership style on the performance of employees of the Karawang Hospital Medical Record Installation. The data was collected through the distribution of questionnaires and carried out on 42 employees of the Medical Record Installation at the Karawang Hospital. Analysis of the data in this study using SPSS version 15. The sampling technique used is the census method and the data testing technique used in this study includes validity tests with statistical analysis, reliability tests with Cronbach's Alpha. F test and t test to test and prove the research hypothesis. The results of the analysis show that work motivation and leadership style have a significant influence on employee performance. Keywords: Work Motivation, Leadership Style, Employee Performance.